2018
DOI: 10.1075/swll.17.10tho
|View full text |Cite
|
Sign up to set email alerts
|

Learning to read in a digital world

Abstract: Understanding how to best support children as they learn to read in an increasingly digital world involves recognizing the many child-and text-related aspects of children's digital reading experience. In the current chapter, we consider how children's reading skills, goals, as well as the properties of digital text influence children's reading development in digital environments. We further discuss how schools, parents, media creators, and policy makers can help shape children's reading experience in digital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…Moreover, with regard to digital narratives, previous research has shown that particularly enhanced e-books that include sound or dynamic visual images could facilitate absorbed reading experiences even better than traditional print (Schlochtermeier et al, 2015). In the light of increasing digitization, literary reading on screen is likely a long-term phenomenon (Schwabe et al, 2021), yet so far, the impact of digitization on the experience of narrative texts has been debated mostly on a theoretical level, and scholars underline the need for more interdisciplinary empirical research on the literary reading experience (Mangen, 2016;Thomson et al, 2018). Overall empirical research on reader experiences of digital fiction is scarce (Bell et al, 2018), and despite their potential to make reading more appealing, the particular effects of enhanced e-books on absorbing reading experiences of evolving readers have not yet been empirically measured in earlier studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, with regard to digital narratives, previous research has shown that particularly enhanced e-books that include sound or dynamic visual images could facilitate absorbed reading experiences even better than traditional print (Schlochtermeier et al, 2015). In the light of increasing digitization, literary reading on screen is likely a long-term phenomenon (Schwabe et al, 2021), yet so far, the impact of digitization on the experience of narrative texts has been debated mostly on a theoretical level, and scholars underline the need for more interdisciplinary empirical research on the literary reading experience (Mangen, 2016;Thomson et al, 2018). Overall empirical research on reader experiences of digital fiction is scarce (Bell et al, 2018), and despite their potential to make reading more appealing, the particular effects of enhanced e-books on absorbing reading experiences of evolving readers have not yet been empirically measured in earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive research on narrative absorption in novels, movies, or video games over the last two decades (e.g., Bezdek & Gerrig, 2017;Busselle & Bilandzic, 2008;Tal-Or & Cohen, 2010), in which the origin and effects of absorption experiences have been described, Thomson et al (2018) underline the need for more developmental research on how narrative absorption in written narratives may vary as a function of reading technology and nonlinearity: " [with regard to] hyperlinked text requiring frequent within-text decisions as to what content to read next, an open question for the field is the degree to which digital text can support 'immersive' reading experiences that have traditionally been experienced when reading print-based literary texts." Indeed, research to date has not yet empirically determined whether the theoretical assumptions (Mangen, 2008;Mangen & van der Weel, 2017), and the findings from scarce empirical studies (Miall, 2004;Miall & Dobson, 2001) on absorption in early hypertext fiction read on computer screens hold true for modern day multimodal nonlinear narrative, which can be read on portable reading devices, while the differences between digital reading and reading on paper continue to diminish (Clowes, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Se trata más bien de la interacción entre las características de los textos digitales con las preferencias lectoras y el rendimiento del lector. Además, hay que tener en cuenta que el entorno digital cambia constantemente (Thomson et al, 2018) y, por tanto, el proceso de alfabetización debe actualizarse periódicamente si se quiere adoptar esta medida como remedio al desapego hacia la lectura digital.…”
Section: Alfabetizaciónunclassified
“…Por Retención se entiende la habilidad del lector en recordar el contenido de un texto. Esto proceso resulta complejo en el entorno digital debido a que la lectura se caracteriza por ser un espacio multidimensional y cognitivamente crucial para el lector (Thomson et al, 2018). De hecho, la lectura digital afecta los criterios de las «funciones ejecutivas» (Wylie et al, 2018) en comparación con la lectura tradicional, alterando específicamente la atención, la memoria, el control ejecutivo y la metacognición del lector.…”
Section: Código Retenciónunclassified